Fatwa dan Produk Hukum dalam Perspektif Ushul Fiqh: Analisis Majelis Taujih Wal Irsyad (MTI) di Lembaga Dakwah Islam Indonesia (LDII) - Mawahib, M. Mahdil; Muttaqin, Amrul (JOM, 2021)
This article delves into the pivotal role of Fatwas and Legal Products issued by Majelis Taujih Wal Irsyad (MTI) within the Lembaga Dakwah Islam Indonesia (LDII) through the lens of Ushul Fiqh. It explores how LDII, as a prominent religious organization in Indonesia, utilizes the Fatwas and Legal Products provided by MTI as fundamental pillars in regulating the religious practices of Muslims. The study's findings underscore LDII's steadfast adherence to the Qur'an and Hadith in formulating its legal framework, while also incorporating various madhhabs recognized by Ahlus Sunnah wal Jamaah, provided they align with the teachings of the Qur'an and Hadith. Unlike some organizations, LDII does not formulate its own fatwas; rather, it derives its legal rulings directly from the Qur'an and Sunnah. The educational approach within LDII emphasizes the significance of students and teachers alike possessing the books being studied, employing the term "manqul" to denote the transfer of knowledge from teacher to student through collaborative study sessions. Furthermore, LDII's adoption of the identity code 313 stems from a historical event—the Battle of Badr—which serves as a symbolic tool to facilitate mutual recognition among LDII members, devoid of any ulterior motives. These findings underscore LDII's commitment to prioritizing the Qur'an and Hadith as the primary sources of authority in legal matters, while also acknowledging the diverse perspectives within Islamic jurisprudence.Ultimately, this research enhances our understanding of the legitimacy and applicability of Islamic law as espoused by LDII, shedding light on its practical implications within the broader religious community.